Acute Hyperglycemia and In-Hospital Mortality in Spontaneous Intracerebral Hemorrhage. (6th January 2023) - Gupta, Himanshu; Beshara, Simon; Katsanos, Aristeidis; Patil, Tushar; Al-Zahrani, Saeed; Chen, Jerry Yeou-Wei; Alharbi, Abdulrahman; Zamir, Nasim; Ng, Kelvin; Kase, Carlos S.; Shoamanesh, Ashkan
ABSTRACT: Hyperglycemia is reported to predict worse outcome in patients with stroke, including intracerebral hemorrhage (ICH). In 83 consecutive cases of ICH at a tertiary stroke center, hyperglycemia (serum glucose >7 mmol/L) compared to normoglycemia at presentation was associated with higher rates of in-hospital mortality (51.2% vs. 26.2%, OR 2.3, CI 1.2–7.6, p = 0.02). The association with in-hospital mortality withstood adjustment for age, ICH volume, intraventricular hemorrhage, and infratentorial ICH location, but not baseline Glasgow Coma Scale. Acute hyperglycemia is associated with in-hospital mortality in spontaneous ICH patients, though this may be an indirect, rather than a causal relationship.